Empowering Communities: A Path to Reducing Domestic Violence through Economic Resilience - Ferry Fathurokhman; Reine Rofiana (Probono and Community Service Journal, 2023)
The Ciboleger Barokah Valley Community, comprising 115 individuals, represents a marginalized Baduy community in Bojong Menteng Village, Leuwidamar District, Lebak Regency. The Baduy tribe adheres to the Sundanese Wiwitan religion, and those who convert to other faiths can no longer live in Kanekes Village, their ancestral home. Most Baduy individuals in Ciboleger Valley lack formal education and employment, often experiencing social isolation and separation from their extended families. These conditions elevate the risk of social issues, including domestic violence, due to economic fragility, as they struggle to meet daily needs. To address these challenges, a program offers financial literacy and legal education. This initiative aims to reduce domestic violence and enhance economic resilience. Financial literacy is delivered through counselling and entrepreneurship training, with a focus on kinca serabi and mustofa potato production by the Dapur Mimih Serang culinary brand. Interactive training engages the local community through discussions, question-and-answer sessions, practical exercises, and business exploration, fostering Self-Help Groups within the community. The program's holistic approach seeks to empower this marginalized community academically, economically, and legally.